Leiomyosarcoma of the prostate a case report of remission for 9 years by radiotherapy - Sakano, Y (Hinyokika kiyo. Acta urologica Japonica, 1995)
A 68-year-old-man with chief complaints of pollakisuria and lower abdominal discomfort was referred to our hospital on September 19, 1983. A histopathological study of the transrectal needle biopsy specimens revealed a malignant tumor of the prostate with spindle-shaped cells. The patient had been considerably improved by radiotherapy. However, 9 years later, the tumor recurred and the histopathological study showed the same findings as the initial biopsy and furthermore the recurrent tumor was diagnosed as a leiomyosarcoma of the prostate by immunohistochemical stain. He was unresponsive to chemotherapy and died 11 years after initial diagnosis